KONSEP KURIKULUM PENDIDIKAN ISLAM MENURUT MUHAMMAD NATSIR - Edy Saputra (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
This article examines the concept of the Islamic education curriculum according to Muhammad Natsir. This study is included in the library research category. The study method used is descriptive-analytical. The primary data in this study came from the book Capita Selecta by Muhammad Natsir. The results of this study indicate that Muhamamd Natsir has made curriculum reforms during his time. The curriculum offered by Muhammad Natsir is an integrated curriculum that integrates religious and general education as the synthesis of the current dichotomy of the Islamic education curriculum.